Civil society : the critical history of an idea - Ehrenberg, John (New York University Press, 2017)
"Provides a comprehensive discussion and analysis of two and a half millennia of Western political theory, as well as what the future may hold for how civil society might be understood. John Ehrenberg analyzes both the usefulness and the limitations of civil society and maps the political and theoretical evolution of the concept and its employment in academic and public discourse. From Aristotle and the Enlightenment philosophers to Black Lives Matter and the Occupy movement, the book provides an indispensable analysis of the possibilities of what this increasingly important idea can, and cannot, offer to contemporary political affairs."--Page [4] of cover.